Risk factors which affect the change of antibiotics in neonatal pneumonia observed in a tertiary care hospital (Northern International Medical College Journal, 2015)
Background : Neonatal pneumonia accounts for significant morbidity and mortality specially in developing countries like Bangladesh. Perhaps because of its etiologic complexity, pneumomia in neonates has been relatively refractory to reduce its severity and improve the prognosis. Re- evaluation of the antibiotic therapy is necessary in patients to have at 48 hours after diagnosis. Physician should suspect inappropriate antibiotic therapy in cases with persistence of symptoms.Objective: This study was carried out to find the risk factors (clinical and laboratory parameters) which affect the change of antibiotic in neonatal pneumonia and its effect on morbidity and mortality .Methodology: This prospective observational study was conducted in Dhaka Shishu (children) Hospital from July 2009 to June 2010. A total of 115 neonates who met the inclusion criteria were enrolled in the study. The neonates were managed using a standard protocol. They were closely followed up to see the outcome with the change in antibiotics.Results : Total 115 neonates were admitted with mean age 16.2±5.9 days, mean weight 2857.6±580.6gm,58% were male & 42% female,26% were preterm & 74% were term and majority of them (73%) were from rural areas. Among the neonates, 36 (31,3%) needed a change in antibiotics. Fever, positive CRP, low O2 saturation, low PaO2 , high alveolar-arterial O2 gradient, low arterial-alveloar O2 tension and low pH were significantly associated with change in antibiotics.Conclusion : Addressing the clinical and laboratory parameters appropriately the change in antibiotic in selected cases can reduce both morbidity and mortality of neonates with pneumonia.Northern International Medical College Journal Vol.6(1) 2014: 21-24